2012
DOI: 10.1002/hipo.22048
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C stimulates HuD‐mediated mRNA stability and protein expression of neurotrophic factors and enhances dendritic maturation of hippocampal neurons in culture

Abstract: HuD protein is an RNA-binding protein involved in post-transcriptional regulation of gene expression for synaptogenesis, neuronal differentiation, and learning and memory, and is up-regulated and redistributed by a protein kinase C (PKC)-dependent pathway in neurons. Here, we show a PKC-regulated mechanism on HuD-mediated mRNA stability and expression of several neurotrophic factors (NTFs) in cultured hippocampal neurons. HuD pull-down assays showed that HuD is associated with brain-derived neurotrophic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 45 publications
4
63
0
1
Order By: Relevance
“…A recent report found a direct link between the antagonistic effects of PKC and CARM1 on HuD function and cell fate (Lim and Alkon 2012). In hippocampal neurons, the study demonstrated using pathway-specific inhibitors that activated PKC isoforms interact and phosphorylate CARM1, which leads to decreased CARM1 methyltransferase activity.…”
Section: Post-translational Control Of Hud Expression and Functionmentioning
confidence: 85%
See 3 more Smart Citations
“…A recent report found a direct link between the antagonistic effects of PKC and CARM1 on HuD function and cell fate (Lim and Alkon 2012). In hippocampal neurons, the study demonstrated using pathway-specific inhibitors that activated PKC isoforms interact and phosphorylate CARM1, which leads to decreased CARM1 methyltransferase activity.…”
Section: Post-translational Control Of Hud Expression and Functionmentioning
confidence: 85%
“…Numerous other ARE-harboring transcripts, such as N-myc and c-myc, were later identified as targets of HuD using similar in vitro approaches, indicating that HuD binds short-lived mRNAs whose protein product functions in cell proliferation (Liu et al 1995;Ross et al 1997). In addition to these transcripts, HuD has been shown to bind and regulate several other mRNAs in vitro and in vivo, many of which encode proteins with important functions in neuronal differentiation such as cell cycle arrest (p21 cip1/waf1 ) (Joseph et al 1998), neuroblast proliferation (MSI-1) (Ratti et al 2006), neuron migration (MARCKS) (Wein et al 2003), neurite extension ([GAP-43] , Tau [Aranda-Abreu et al 1999], and AChE [Cuadrado et al 2003;Deschenes-Furry et al 2006;), synapse formation (NOVA-1) (Ratti et al 2008), and neuronal growth and survival (NGF, BDNF, and NT-3) ( Table 2; Lim and Alkon 2012).…”
Section: Cis-element and Target Mrnas Of Hudmentioning
confidence: 99%
See 2 more Smart Citations
“…Translation of neuronal mRNAs localized in dendrites is controlled by signaling cascades activated by glutamate receptors and BDNF itself (Bramham and Wells, 2007;Leal et al, 2014). Translation of BDNF mRNA requires interaction with the binding protein HuD (also known as ELAVL4), which is mediated by a protein kinase C (PKC)-dependent pathway (Lim and Alkon, 2012), and phosphorylation of the eukaryotic elongation factor (eEF2) by the eEF2 kinase (eEF2K), two key pathways involved in synaptic plasticity (Verpelli et al, 2010). However, it is still unclear how the different signaling cascades controlling translation can regulate BDNF and where these signaling pathways are active in the different subcellular regions.…”
Section: Introductionmentioning
confidence: 99%